MAPPING INDONESIA’S INDIGENOUS SCIENCE AS A SCIENCE LEARNING CONTEXT IN JUNIOR HIGH SCHOOL: A NEW PARADIGM - Arumning Tyas, Rizki; Widhy Hastuti, Purwanti; Rahayu, Dita Puji (E-Journal of Cultural Studies, 2024)
The integration of indigenous science into learning, especially science learning for junior high school students, is very necessary. Indigenous science can be used as a context and source for learning science. Mapping Indonesian’s indigenous science is needed to facilitate educators in utilizing and integrating into learning. This study aimed to: (1) analyze and identify junior high school science subject matter and (2) conduct analysis and identification of ethnoscience that is feasible and suitable to be used as a context for junior high school science learning. This research was conducted through literature studies with primary data sources in the form of junior high school science curriculum documents and secondary data sources in the form of documents, internet, books, proceedings, reputable international journals, international journals, and national journals. The stages of the research carried out are: (1) analyzing and identifying material in junior high school science subjects; (2) selecting and sorting material that has the potential to contain ethnoscience content; (3) make details of the subject matter, and (4) present the analysis result. This study succeeded in identifying 7 (seven) indigenous sciences along with their context and content in junior high school science materials, including: (1) Karapan Sapi Tradition from Madura, East Java; (2) Local Potential of Pottery Handicraft Center; (3) Traditional Dance " Lilin " from West Sumatra; (4) Local potential of "salted eggs" from Brebes, Central Java; (5) " Kayon " Puppet Performance Instrument; (6) Natural Potential " Belik " and (7) Dayak Traditional Clothing: King Bibinge and King Baba. Keywords : Indigenous, Learning Process, Science Education Context.